Functional tuning of A–D–A oligothiophenes: the effect of solvent vapor annealing on blend morphology and solar cell performance1. Issue 26 (14th July 2015) - Schulz, Gisela L.; Löbert, Mirjam; Ata, Ibrahim; Urdanpilleta, Marta; Lindén, Mika; Mishra, Amaresh; Bäuerle, Peter
<x xml:space="preserve">Abstract</x> A series of dicyanovinylene-substituted A–D–A oligothiophenes with cores of varying donor strength were developed for solution-processable organic solar cells, with significant enhancement in power conversion efficiencies upon solvent vapor annealing.